The Power of Screens: Innovations in Teaching English to Young Learners through Educational Videos - Budiarta, Luh Gd Rahayu (Journal of Educational Study, 2024)
Educational videos have transformed language learning by enchanting young learners and changing traditional teaching methods. This study aimed to develop innovative educational videos aligned with the English syllabus for young learners while assessing their impact on language acquisition. Using the ADDIE (Analysis, Development, Design, Implementation, and Evaluation) model, instructional designers created and continually improved English language teaching videos to provide engaging and effective language learning experiences. Data collection instruments included interview guides, document analysis, blueprints, rubrics, and questionnaires. The study produced prototype videos using a discovery-based learning approach, covering topic self-introduction, daily routines, and telling the time. Feedback was gathered from participants using rubrics and questionnaires to evaluate the videos. Analysis revealed that the videos were exceptional teaching and learning resources for fifth-grade elementary school students (30 students). They fostered active engagement, authentic language use, and comprehension development, aligning with the objectives of English language education. This study highlights the transformative potential of educational videos in English language teaching for young learners. By employing the ADDIE model and integrating innovative approaches, educators can create captivating and effective instructional videos that meet the needs of young language learners. The findings underscore the value of incorporating such videos in English language classrooms, enhancing language proficiency and facilitating meaningful language acquisition.